2013
DOI: 10.1002/ajmg.a.36325
|View full text |Cite
|
Sign up to set email alerts
|

Narrowing of the responsible region for severe developmental delay and autistic behaviors in WAGR syndrome down to 1.6 Mb including PAX6, WT1, and PRRG4

Abstract: Interstitial deletions of the 11p13 region are known to cause WAGR (Wilms tumor, aniridia, genitourinary malformation, and "mental retardation") syndrome, a contiguous gene deletion syndrome due to haploinsufficiencies of the genes in this region, including WT1 and PAX6. Developmental delay and autistic features are major complications of this syndrome. Previously, some genes located in this region have been suggested as responsible for autistic features. In this study, we identified two patients who showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0
7

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 14 publications
4
16
0
7
Order By: Relevance
“…WAGR patients exhibit mental retardation and sometime autistic phenotypes. There are literatures reporting mutations related with PAX6 gene in patients with ASD, intellectual disabilities, and/or aggressiveness [2832]. 11p13 region is considered to be related with ASD from an initial GWAS study by The Autism Genome Project Consortium [75, 76].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…WAGR patients exhibit mental retardation and sometime autistic phenotypes. There are literatures reporting mutations related with PAX6 gene in patients with ASD, intellectual disabilities, and/or aggressiveness [2832]. 11p13 region is considered to be related with ASD from an initial GWAS study by The Autism Genome Project Consortium [75, 76].…”
Section: Discussionmentioning
confidence: 99%
“…Human PAX6 gene was originally identified as a responsible gene for aniridia in the chromosome region 11p13 that is responsible for WAGR (Wilim’s tumor, Aniridia, Genitourinary malformations and mental Retardation) syndrome [26, 27]. Since then, several reports showed that mutations in PAX6 gene are risk factors for ASD and related disorders [2832]. Furthermore, several studies have shown structural brain abnormalities in people with mutations in PAX6 gene [3336].…”
Section: Introductionmentioning
confidence: 99%
“…This case differs from the “classical” PAX6 gene deletions causing aniridia alone, as only the 3′ enhancer elements are deleted in this case and ELP4 is included [Davis et al., ]. A more recent paper also describes a family with deletion of PAX6 and ELP4 with aniridia, ptosis, and mental retardation [Hu et al., ], and furthermore, a region responsible for the autistic behavior and severe developmental delay of WAGR syndrome has been narrowed down to 1.6 Mb including ELP4 and PAX6 on 11p13 [Yamamoto et al., ]. ELP4 has previously been associated with the electroencephalographic (EEG) signature of the common childhood epilepsy rolandic epilepsy (RE) [Strug et al., ], and both EEG abnormalities as well as epilepsy are frequent in ASD and language impairments [Nasr et al., ; Parmeggiani et al., ].…”
Section: Introductionmentioning
confidence: 99%
“…Другие костные аномалии В редких случаях агенез локтевой кости [13], гипоплазия бедренной кости и диффузная остеопения, кифозы [29] Встречаются удвоение больших пальцев ног, отставание в костном развитии, деминерализация костей, почти всегда есть отставание в росте [40,[44][45][46] Дефекты соединительной ткани Единичные случаи паховой и пупочной грыжи [40] Часто (6/18): паховая, пупочная, а также грыжа диафрагмы, врожденный вывих бедра, дефекты межпредсердной перегородки [40,47] Аномалии ушной раковины В единичных случаях [29] Часто (7/12) [40] Ожирение Индекс массы тела и частота ожирения достоверно выше среди больных аниридией, чем среди их здоровых сибсов. Встречаются висцеромегалия и гигантизм [10] Хотя пациенты с синдромом имеют пониженный вес при рождении [41], в значительной доле случаев с возрастом развивается ожирение (18%) [2,48], гемигипертрофия [14,40] Сахарный диабет с ранним началом, нарушение толерантности к глюкозе…”
Section: врожденная аниридия синдром Wagrunclassified
“…Предполагается, что область длиной примерно в 1,5 млн пар нуклеотидов, обязательно захватывающая оба гена -PAX6 и WT1, является критичной для формирования всех составляющих синдрома [45]. Синдром встречается почти исключительно в спорадических случаях (в мировой литературе описано всего 2 семейных случая) [14], однако у одного из родителей возможен гонадный мозаицизм по делеции или сбалансированная хромосомная перестройка, нарушающая сегрегацию хромосом при созревании гамет и приводящая к частичной анеуплоидии у потомков.…”
Section: врожденная аниридия в составе синдрома Wagrunclassified